The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/opth.s36792
|View full text |Cite
|
Sign up to set email alerts
|

Superior segmental optic nerve hypoplasia accompanied by progressive normal-tension glaucoma

Abstract: This is the first case report of a superior segmental optic hypoplasia (SSOH) combined with normal-tension glaucoma accompanied by a progressive glaucomatous visual field defect. A 40-year-old man, incidentally diagnosed as having bilateral SSOH, had disc hemorrhage associated with expansion of the width of a retinal nerve fiber layer defect and deterioration of a visual field defect in the right eye during the follow-up period. His left eye showed a stable visual field. The diurnal variation in intraocular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…SSOH is non-progressive, and no treatment is necessary. There have been case reports of SSOH that is also accompanied by NTG with progressive glaucomatous visual field defect [7].…”
Section: Discussionmentioning
confidence: 99%
“…SSOH is non-progressive, and no treatment is necessary. There have been case reports of SSOH that is also accompanied by NTG with progressive glaucomatous visual field defect [7].…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is one of the risk factors of glaucoma [ 20 , 21 ], but no previous reports suggested that high myopia may be associated with glaucomatous progression in SSOH eyes. In one previous case report of progressive SSOH, the patient had a high myopia of −8.0 D [ 8 ], so it might not be coincidence that glaucoma with SSOH had a high myopia, and it seems necessary to evaluate whether coexistence of SSOH and high myopia can lead to glaucomatous changes or progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not easy to differentiate the two diseases because SSOH and glaucoma have similar features, such as localized RNFL thinning and neuroretinal rim thinning [ 6 ]. Furthermore, the two diseases sometimes exist simultaneously [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While SSOH is nonprogressive in nature and is an important entity in the differential diagnosis of childhood glaucoma, there is an isolated case report of SSOH accompanied by NTG in an adult after five years of annual follow up, necessitating long-term monitoring even in low-risk patients [7]. Sequential SD-OCT surveillance and visual field testing are useful tools in detecting progressive glaucomatous changes.…”
Section: Discussionmentioning
confidence: 99%